The Role of Kiai in Prophetic Education and Cultural Brokerage - Darain, A. Sa’dud; Anshari, Achmad; Sa’diyah, Halimatus (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to reveal the role of kiai in implementing prophetic educational values ​​at the Nahdhatut Ta'limiyah Islamic Boarding School, Pamekasan Regency, and analyze the function of kiai as a cultural broker in maintaining a balance between religion, local culture, and the demands of modernity. This study uses a qualitative approach with data collection methods in the form of participatory observation, in-depth interviews, and documentation studies. The results show that KH. M. Musleh Adnan applies prophetic educational leadership based on three main pillars, namely humanization (amar ma'ruf), liberation (nahi munkar), and transcendence (faith in Allah). These three pillars are internalized through educational strategies that include exemplary behavior (uswah hasanah), habituation (ta'wid), and continuous mentoring (muraqabah). In practice, kiai not only act as educators and spiritual leaders, but also as cultural mediators capable of integrating Islamic teachings with local Madurese traditions, such as tahlilan (religious gatherings), haul (haul), and public religious studies (pengajian). This integration demonstrates a contextual form of prophetic education, where local culture is positioned as a medium for da'wah (Islamic preaching) and a means of character formation for students. Furthermore, KH. M. Musleh Adnan encourages students to have a critical, adaptive, and open attitude towards technological developments and social change, without losing the foundation of Islamic spiritual and moral values. With this approach, the Nahdhatut Ta'limiyah Islamic Boarding School has developed as a humanistic, transformative, and moderate educational space, and functions as a center for the culturalization of prophetic values ​​relevant to the context of contemporary society.